A 3‐year longitudinal study of skeletal effects and growth in children after kidney transplantation. (11th July 2018) - Swolin‐Eide, Diana; Hansson, Sverker; Magnusson, Per
Abstract: This prospective study investigated growth and skeletal development for 3 years after kidney transplantation in pediatric patients, 3.4‐15.0 years of age. Growth, BMD, bone resorption markers (CTX and TRACP5b), bone formation markers (PINP, ALP, and osteocalcin), PTH, and vitamin D were assessed at start, 3, 12, and 36 months after transplantation. Median GFR was 63 (range 37‐96) mL/min/1.73 m 2 after 3 years. The median height SDS increased from −1.7 to −1.1, and median BMI SDS increased from −0.1 to 0.6 over 3 years, which shows that transplantation had a favorable outcome on growth. Fat mass increased after transplantation at all time points, whereas lean mass increased after 1 year and 3 years. Total BMC increased at all time points. No changes were observed for total BMD. Bone resorption markers decreased initially after 3 months and remained stable throughout the study, whereas the bone formation markers decreased initially, but successively increased over the study period. In conclusion, this study demonstrates that height SDS and BMI SDS increased, along with the increased formation markers that reveal a positive bone acquisition after kidney transplantation, which was reflected by the significant increase in total body BMC.